"We Are Not Starving:" Challenging Genetically Modified Seeds and Development in Ghana. (3rd June 2018) - Rock, Joeva
Abstract: In the last decade, the number of African countries researching and growing genetically modified seeds (GMOs) has increased fourfold. These efforts are backed by an international consortium of donors who broker agreements between biotechnology companies and African state scientists to lease genetic material for use. Given the involvement of African scientists, proponents argue that these projects are homegrown and necessary to feed the African continent. However, in Ghana, where GM cowpea and rice are currently under field trial, both Ghanaian scientists and anti‐GMO activists are unsatisfied with donor‐constructed realities. Instead, these unlikely bedfellows challenge the discourses that circulate through international development circuits by pointing to a history of both colonial exploitation and sovereign dreams. By doing so, Ghanaian scientists and activists articulate alternative visions for a food sovereign, postcolonial future.